THE INFLUENCE OF ELECTRONIC WORD-OF-MOUTH, PRICE, AND PRODUCT KNOWLEDGE ON CUSTOMER LOYALTY - Gideon christopher sondakh gideon; James D. D. Massie; Maria V. J. Tielung (Universitas Sam Ratulangi, 2023)
Customer loyalty influences the journey of business success in the future. Electronic Word-Of-Mouth, Price, Product Knowledge are the parts and determine on Customer Loyalty. The purpose of this study was to researcher know how electronic word-of-mouth, price, product knowledge influence customer loyalty study case YOIIIDRINK MDC. Respondents based on who buy more than once, Boba drink fan, consumer aged 11-25 years domiciled in Manado. The population in this study were 100 respondents. The sample in this study used purposive sampling. The analyzer uses multiple linear regression. Hypothesis testing used the T test and F test. The results showed that how satisfaction customer loyalty about electronic word-of-mouth, price, product knowledge and the owner to increase improvement in product must take care of several aspects provided to provide and determine the level of customer satisfaction about the product Keywords: electronic word-of-mouth, price, product knowledge, customer loyalty